1991
DOI: 10.1007/bf01744261
|View full text |Cite
|
Sign up to set email alerts
|

Development of floor plate, neurons and axonal outgrowth pattern in the early spinal cord of the notochord-deficient chick embryo

Abstract: The notochord is probably involved in the development of the neural tube. In this study, a fragment of caudal notochord was extirpated in ovo from chick embryos at 1.5 days of incubation. At 4.5 days a distinct notochord-deficient region at thoracolumbar level was found. Profound effects were seen, especially at the cranial site of this region. Somites were smaller than normal, or even not recognizable, and in some cases the myotomes were fused in the midline. The spinal cord appeared reduced in size and lacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…Removal of the notochord results in the fusion of the right and left dermomyotomes beneath the neural tube (Christ, 1970;van Straaten and Hekking, 1991), and outgrowth of axonal roots in the ventral midline (van Straaten and Hekking, 1991). Disturbed axonal guidance is also found in the notochord defective mutant of the mouse, Dunforth's short-tail (Bovolenta and Dodd, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the notochord results in the fusion of the right and left dermomyotomes beneath the neural tube (Christ, 1970;van Straaten and Hekking, 1991), and outgrowth of axonal roots in the ventral midline (van Straaten and Hekking, 1991). Disturbed axonal guidance is also found in the notochord defective mutant of the mouse, Dunforth's short-tail (Bovolenta and Dodd, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This idea was initially based on experiments performed in the chick in which the notochord was removed in the posterior region of the embryo. Removal of the notochord results in the absence of floor plate and motoneurons on a short segment located in the caudalmost part of the operated territory (13)(14)(15). The conclusion was drawn that the notochord is inducing a floor plate in the midline of the neural plate.…”
mentioning
confidence: 92%
“…The notochord extirpation experiments, which suggested that floor plate differentiation was the result of an induction, were generally performed in chicken embryos at stages ranging from 10-to 20-somite stage (ss) (13)(14)(15)(28)(29)(30). The notochord was removed either mechanically or enzymatically from the level of the last formed somites down to Hensen's node, which was in principle excluded from the operation.…”
mentioning
confidence: 99%
“…The importance of the notochord in dorsoventral patterning of the neural tube has been highlighted in studies utilising surgical manipulation of early embryos (Kitchin, 1949;van Straaten et al, 1985van Straaten et al, , 1988van Straaten and Drukker, 1987;van Straaten and Hekking, 1991;Yamada et al, 1991). Removal of the notochord results in the loss of the floor plate (van Straaten and Hekking, 1991) and the adjacent bilaterally located motor neuron pools (Yamada et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the notochord results in the loss of the floor plate (van Straaten and Hekking, 1991) and the adjacent bilaterally located motor neuron pools (Yamada et al, 1991). As a result, cells throughout the neural tube appear to be left with a dorsal phenotype (Yamada et al, 1991).…”
Section: Introductionmentioning
confidence: 99%